The influence of coffee clones and postharvest methods on the physical quality of eight clones of local robusta coffee in West Lampung, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Analianasari, Murhadi M, Nurdin SU, Utomo TP, Suhandy D. 2023. The influence of coffee clones and postharvest methods on the physical quality of eight clones of local robusta coffee in West Lampung, Indonesia. Biodiversitas 24: 5779-5787. One of the qualities of coffee is a physical characteristic that can be seen directly as a determinant of the coffee bean's price. This study consisted of eight clones of robusta coffee picked red, which was processed using the postharvest method (natural, honey, and full wash) with three repetitions, then evaluated based on the physical attributes of the coffee beans (moisture content, weight of 100 coffee beans, length and the width of the coffee beans, the percentage of passing through the Sieve, and the number of coffee bean defects). The results showed that most of the physical quality parameters of clones from local Robusta coffee varieties were carried out using the postharvest method and planted in West Lampung statistically different (P